Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2010
DOI: 10.1371/journal.pone.0011584
|View full text |Cite
|
Sign up to set email alerts
|

LRP-1 Promotes Cancer Cell Invasion by Supporting ERK and Inhibiting JNK Signaling Pathways

Abstract: BackgroundThe low-density lipoprotein receptor-related protein-1 (LRP-1) is an endocytic receptor mediating the clearance of various extracellular molecules involved in the dissemination of cancer cells. LRP-1 thus appeared as an attractive receptor for targeting the invasive behavior of malignant cells. However, recent results suggest that LRP-1 may facilitate the development and growth of cancer metastases in vivo, but the precise contribution of the receptor during cancer progression remains to be elucidate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
87
0
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 82 publications
(94 citation statements)
references
References 67 publications
6
87
0
1
Order By: Relevance
“…‫,ءء‬ P Ͻ 0.01. consistent with the ability of LRP-1 to control signaling pathways, contributing to the aggressive behavior of tumor cells. We have recently demonstrated that LRP-1 sustains tumor progression by mediating the induction of an ERK cascade and inhibition of JNK phosphorylation in thyroid carcinoma (28). Others have shown that binding of the protease nexin 1 to LRP-1 stimulates the ERK pathway, leading to matrix metalloproteinase 9 (MMP-9) expression and metastasis development (17).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…‫,ءء‬ P Ͻ 0.01. consistent with the ability of LRP-1 to control signaling pathways, contributing to the aggressive behavior of tumor cells. We have recently demonstrated that LRP-1 sustains tumor progression by mediating the induction of an ERK cascade and inhibition of JNK phosphorylation in thyroid carcinoma (28). Others have shown that binding of the protease nexin 1 to LRP-1 stimulates the ERK pathway, leading to matrix metalloproteinase 9 (MMP-9) expression and metastasis development (17).…”
Section: Discussionmentioning
confidence: 99%
“…We recently characterized the intracellular molecular signaling relays involved in the LRP-1-mediated stimulation of cancer cell invasion (28). We thus identified the LRP-1 ␤-chain as a main docking site for mitogen-acti- (Fig.…”
Section: Ftc-133 Carcinoma Cell Attachment Is Increased By Both Rap Tmentioning
confidence: 99%
“…LRP1 is a ubiquitously expressed endocytic receptor belonging to the LDL-receptor family (Herzand Strickland, 2001). LRP-1 can promote cancer cell invasion via supporting ERK and inhibiting JNK signaling pathways (Langlois et al, 2010), and has been identified as a molecular signaling partner for plateletderived growth factor receptor (PDGFR) (Boucherand Gotthardt, 2004). Moreover, PDGFR is considered as a therapeutic target and a prognostic marker for imatinib mesylate therapy in OS (Kubo et al, 2008).…”
Section: Discussionmentioning
confidence: 99%
“…Subsequent protein homology searches identified a 19-amino-acid sequence called Angiopep-2 that exhibits high transcytosis capacity (18), crossed the BBB through an LRP-1-mediated mechanism (25), and distributed broadly throughout brain parenchyma (18,26). In addition to its well-determined role in ligand binding and endocytosis, LRP-1 has emerged as a central molecular regulator of cytoskeleton organization and adhesive complex turnover in malignant cells (27).…”
Section: Angiopep-2mentioning
confidence: 99%